Ronnie James Dio: the man on the silver mountain - Joe Weber (Journal of Maps)
Ronald James Padovana was born 10 July 1942. In 1957 he began what became a fifty three-year career in music career. In 1960 he began singing under the name Ronnie Dio, and then Ronnie James Dio. Under this name he became an iconic hard rock vocalist, performing with numerous bands including Rainbow (1974–1979), Black Sabbath (1979–1982, 1992, and 2006–2010), and his own band Dio (1982–2004). Before his untimely death on 16 May 2010, he had performed 2293 shows in 627 cities in forty-eight countries around the world. He sold over 6,500,000 albums. This map shows every city he performed in during his career at a scale of 1:74,380,000, along with three insets at varying scales highlighting performances within different world regions, and a series of 28 separate inset maps at a scale of 1:575,000,000 showing the cities he performed in during each concert tour.